PENINGKATAN KEMAMPUAN GURU DALAM MENERAPKAN TEORI BELAJAR KONSTRUKTIVISME MELALUI SUPERVISI AKADEMIK PENDEKATAN DIRECT INSTRUCTION - Ahmad Basori (Manajer Pendididikan, 2016)
The type of this research is to improve of teacher’s ability in implementing constructivism of learning theory. The method used through academic supervision approach direct instruction which held by four step, that is: review, presentation, practice guided and selfsupporting practice. This research was held in SMKN 2 Bengkulu City. The result of data analysis is the average of teacher’s ability in cycle I: test result is 72,04; writing lesson plan is 74,89 and implementing contructivism learning is 70,36. While the analysis result in cycle II: test result is 87,78, writing lesson plan is 89,11 and implementing constructivism learning is 86,66. The average score of teacher’s ability increase from cycle I to cycle II.Keywords: constructivism, learning theory, academic supervision, direct instruction